MENINGKATKAN PEMAHAMAN KONSEP STRUKTUR BUNGA DAN FUNGSINYA DENGAN PENGGUNAAN METODE TUTOR SEBAYA KELAS IV SD - Hadi Rohyana, Hadi Rohyana (JISPE Journal of Islamic Primary Education, 2021)
This classroom action research aims to determine student attitudes in the learning process and improve students' understanding of the concept of flower structure and function by using peer tutoring methods in science lessons in fourth grade elementary school. This research is a classroom action research (CAR) conducted in the classroom (classroom action research), the Class Action Research (CAR) method in the form of a cyclical assessment in four stages, namely (1) Planning (2) Action (3) Observation (4) Reflection. By using data collection in the form of observation, evaluation questions. The data analysis technique was using the average value and percentage of all class IV groups at SDN Pelandakan I Cirebon City. The results of the analysis show that with the use of peer tutoring methods, student activities in the learning process experience changes in each cycle, the highest cycle I is only 55%, the second cycle is 75% the highest, and the third cycle is 95% the highest. And the percentage value in the first cycle of student evaluation is 67%, the second cycle is 82%, and the third cycle is 97% while the percentage of teacher performance in the first cycle is 88.8%, the second cycle is 92.5%, and the third cycle is 96, 2%. This shows that the use of peer tutoring methods can improve the understanding of the concept of the structure of interest and its function in the fourth grade students of SDN Pelandakan I, Cirebon City.